Quantitative estimation of muscle fatigue on cyclic handgrip tasks - Yewguan, Soo; Masao, Sugi; Hiroshi, Yokoi; Tamio, Arai; Ryu, Kato; Jun, Ota (2012)
A recovery model is proposed to represent the relationship between the muscle fatigue and the rest time. Three experiments were conducted at 50% MVC with the contraction time of 10 s, 30 s and 50 s. Every experiment consists of 5 handgrip tasks with different rest interval. The maximal isometric forces during the pre-fatigue and post-fatigue were recorded to compute the muscle fatigue developed from each handgrip tasks. An exponential function is used to model the relationship between the muscle recovery and rest interval. With this model, the amount of muscle fatigue that is recovered given the rest duration can be estimated. The results suggest that the rate of muscle recovery is correlated to the degree of muscle fatigue at any particular moment, regardless the contraction level or contraction time of the tasks. It is demonstrated that the performance is not significant improved by increasing the number of experiments during calibration process. After that, the recovery model is integrated with the existing fatigue index proposed previously. This is then evaluated on cyclic handgrip tasks. The results show that during the high repetitive motion tasks, the effect of muscle recovery is essential to be taken into consideration for quantifying the degree of muscle fatigue. In average, the estimation error is between 5% MVC, comparing between the estimated value and the force loss measured using dynamometer. This concludes the effectiveness of utilizing force loss as the index to quantify the muscle fatigue and recovery.